STRATEGIES TO INCREASE ELECTRIC CAR PURCHASE INTEREST THROUGH MODERATED TRUST IN ELECTRIC CAR BRAND EQUITY IN EAST JAVA - Rinto Harno; Aminullah Assagaf; Sukesi, Sukesi (International Journal of Social Science, 2025)
The objective of this study was to analyze the influence of Environmental Concern, Innovation, Social Media Effectiveness, Brand Image, and Green Product Awareness on Purchase Intention through Trust, moderated by Brand Equity, among electric car consumers in East Java. This study used causality, using primary and secondary data sources. The sample population was 195 electric car consumers in East Java. The analytical technique chosen to analyse the data and test the hypotheses in this study was the Structural Equation Model. The results of the study prove that Environmental Concern has a positive but insignificant effect and Innovation has a negative but insignificant effect on Consumer Trust; while Social Media Effectiveness, Brand Image and Green Product Awareness have a positive and significant effect on Consumer Trust; Environmental Concern has a negative but insignificant effect and Innovation has a positive but insignificant effect on Consumer Purchase Intention; while Social Media Effectiveness has a negative but significant effect and Brand Image has a positive but significant effect on Consumer Purchase Intention; except that Green Product Awareness has a positive but insignificant effect on Purchase Intention; Trust has a positive but significant effect on Consumer Purchase Intention; and Trust has a negative but insignificant effect on Purchase Intention moderated by Consumer Brand Equity.